2007
DOI: 10.1016/j.febslet.2007.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a fragment of the cannabinoid CB1 receptor C‐terminus with arrestin‐2

Abstract: Desensitization of the cannabinoid CB1 receptor is mediated by the interaction with arrestin. In this study, we report the structural changes of a synthetic diphosphorylated peptide corresponding to residues 419-439 of the CB1 C-terminus upon binding to arrestin-2. This segment is pivotal to the desensitization of CB1. Using high-resolution proton NMR, we observe two helical segments in the bound peptide that are separated by the presence a glycine residue. The binding we observe is with a diphoshorylated pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…The C-terminal tagging of β-arr1 is also not likely to cause the lack of the signal, as both β-arr1-Rluc and β-arr1-GFP constructs could be successfully used to detect β-arr1 recruitment to AT 1 R and β 2 AR. In a previous study, Bakshi et al have shown using nuclear magnetic resonance (NMR) that a C-terminal fragment of CB 1 R is able to bind β-arr1 (Bakshi et al, 2007). Our data suggest that such binding between the two molecules, even if present, must be very weak compared to β-arr2, when tested with native proteins in living cells.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…The C-terminal tagging of β-arr1 is also not likely to cause the lack of the signal, as both β-arr1-Rluc and β-arr1-GFP constructs could be successfully used to detect β-arr1 recruitment to AT 1 R and β 2 AR. In a previous study, Bakshi et al have shown using nuclear magnetic resonance (NMR) that a C-terminal fragment of CB 1 R is able to bind β-arr1 (Bakshi et al, 2007). Our data suggest that such binding between the two molecules, even if present, must be very weak compared to β-arr2, when tested with native proteins in living cells.…”
Section: Discussionsupporting
confidence: 46%
“…As described in the introduction, the binding between β-arr2 and CB 1 R as well as a role for β-arrestins in the desensitization of CB 1 R have been demonstrated by former studies (Bakshi et al, 2007;Daigle et al, 2008aDaigle et al, , 2008bJin et al, 1999;Kouznetsova et al, 2002;Nguyen et al, 2012;Singh et al, 2011). Therefore, the role of β-arr2 in CB 1 R endocytosis may seem to be a logical consequence of its recruitment to the receptor.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, probable G-protein-coupled receptor kinase phosphorylation sites have been identified Jin et al, 1999;Daigle et al, 2008) and isolated fragments of the CB 1 R C-terminus can bind to b-arrestins (Singh et al, 2011;Bakshi et al, 2007) and GASP1 (Martini et al, 2007). Prolonged agonist exposure downregulates CB 1 Rs expressed in HEK-293 (Shapira et al, 2003) but not N18TG2 cells (McIntosh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Arrestin-1 (or visual arrestin) and arrestin-4 (or cone arrestin) modulate the action of rhodopsin (10,11) and arrestin-2 and arrestin-3 modulate nonretinal GPCRs (12,13). Recently, desensitization of the CB1 receptor was reported to be mediated by the interaction of the COOH-terminal residues (419-439) of CB1 with arrestin-2 (14), indicating that CB1 and CB2 might act as photoreceptors in nonretinal tissues. However, a role for CB1 and CB2 in skin cancer has not been reported.…”
Section: Introductionmentioning
confidence: 99%